The Relationship Between Learning Process Management and Improving Santri’s Life Skills at Darunna’im Islamic Boarding School in Lebak Regency - Ahmad Fitriyadi Sari; Encep Syarifudin; Muhajir (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study is motivated by a decrease in learning process management and an increase in students’ skills at the Darunna’im Islamic Boarding School, Lebak Regency, Banten. Darunna’im boarding school is part of the institution that implements entrepreneurship skills education. As a form of self-development and preparing students to have an entrepreneurial spirit. The results of the entrepreneurship skills program at the Darunna’im Islamic Boarding School are carried out every day as a form of training and self-development for students for the future. Researchers are interested in conducting research related to process management and improving the skills of students in the Darunna’im Islamic boarding school program. This study uses a quantitative approach, namely research that is used to examine certain populations and samples and uses data collection with research instruments that aim to test the hypotheses that have been set. Based on the research results, it is known that the relationship between process management and the improvement of students’ skills can be concluded that there is a relationship between process management and the improvement of the life skills of students at the Darunna’im Islamic boarding school. a positive relationship is indicated by a correlation coefficient of 0.322 and a determination coefficient of 10.4%. This means that the better the process management, the better the students’ life skills will improve.